INCREASING THE CULTIVATION AND DEVELOPMENT OF THE BEEF CATTLE FEED BASE OF THE KALNZIEDI FARM BY REDUCING GHG EMISSIONS - Kivleniece, Žaklīna; Kaša, Marlinda (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
The 21st century has brought a number of challenges to the world that humanity has to face. Climate change is one of them and the world community must do everything it can to improve the current situation. Scientists have shown that the main cause of climate change is the increasing concentration of greenhouse gases (GHGs) in the atmosphere, driven by human economic activity. The environmental impact of the agricultural sector, in the form of increasing GHG emissions, is becoming more pronounced and farmers need in-depth knowledge of the greenhouse gas emissions from agricultural activities and their potential reduction on farms. This is all the more so as EU support for farms is planned to be linked to measures taken to reduce GHG emissions.